Exploring the values of the local wisdom of kediri through harinjing and ceker inscription - Kurnia Ita; Laila Alfi (SHS Web of Conferences, 2018)
Indonesia needs human resources in sufficient quantity and quality as a major supporter of development. To fulfill these human resources, education has a very important role is character development. One effort that can be done by the people of Kediri as an effort to build Indonesia is to use the values of local wisdom as a force. This values can be explored from Harinjing and Ceker Inscription which is located in Kediri, East Java. This research uses qualitative approach with descriptive method. The research purpose is to explore the potentials of local wisdom of Kediri people through (1) the history of Harinjing Inscription and (2) the history of Ceker Inscription. The results of this research that (1) The construction of embankments and holy buildings on the Serinjing River and the making of irrigation systems in Siman, Kepung, Kediri by Bhagawanta Bari proves that since the time of the kingdom, the people of Kediri have a caring to environmental and social, mutual cooperation, and religious character; (2) The people of Kediri also has the character of love of the homeland and faithful. This is evidenced through the inscriptions in Ceker found in the Sukoanyar, Mojo, Kediri.